Kajian Pendapat Komunitas Tentang Video Yang Berjudul Banyak Yang Salfok Tentang Kandang Ayam Kami - Tina Kartina; Nanang Trenggono; Nina Yudha Aryanti (STAI Bumi Silampari, 2026)
Social interaction through social media, including social media usage, has become a habit in today's digital society. People are connected to each other, including friends and family. Likewise, the Instagram community bu_utig engages in discussions within a single social media space, @bu_utig. The purpose of this research is to describe a community opinion survey on a video titled